EXPOSURE LEVELS OF PATIENTS DURING COMPUTED TOMOGRAPHY IN MEDICAL ORGANIZATIONS OF SAINT-PETERSBURG AND LENINGRAD REGION - A. A. Bratilova; V. Yu. Golikov; S. A. Kalnitsky (Радиационная гигиена, 2015)
Were carried out the selective investigation of the adult patients exposure levels during radiological diagnostic  procedures  with  the  use  of  17  CT  scanners  in  15  medical  organizations  of  Saint-Petersburg  and Leningrad region in 2009–2012. We collected the data on technical parameters of the X-ray computed tomography examinations affecting the level of patient exposure. The effective doses were calculated for scanning of different areas of the patient's body (skull, thorax, abdomen and pelvis). Their mean values were in the range from 0,2 mSv to 31 mSv per examination. The highest doses were observed during the investigation of the abdomen and pelvis. Preliminary values of diagnostic reference levels are proposed for medical organizations of Saint-Petersburg andLeningrad region on the basis of investigation results. These values are defined as the 75% quantile in the distribution  of  dose  length  product  values.  Diagnostic  reference  levels  values  obtained  in  the  investigation  are comparable with the corresponding values currently accepted in the foreign medical practice.